2009
DOI: 10.1186/1471-2180-9-208
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of ribosomal RNA operon copy number distribution

Abstract: BackgroundResults of microbial ecology studies using 16S rRNA sequence information can be deceiving due to differences in rRNA operon copy number and genome size of the detected organisms. It therefore will be useful for investigators to have a better understanding of how these two parameters differ in various organism types. In this study, the number of ribosomal operons and genome size were separately mapped onto a Bacterial phylogenetic tree.ResultsA representative Bacterial tree was constructed using 31 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The expected variability was calculated from the consensus models (c). (28,42). Currently, it is common practice to describe the composition of a microbial community using 16S gene composition rather than cell composition.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The expected variability was calculated from the consensus models (c). (28,42). Currently, it is common practice to describe the composition of a microbial community using 16S gene composition rather than cell composition.…”
Section: Downloaded Frommentioning
confidence: 99%
“…By contrast, more complex traits such as oxygenic photosynthesis or sulfate reduction involve many more genes and show phylogenetic conservation at much deeper taxonomic levels (80% and 92.2% mean 16S rRNA sequence identity, respectively; Martiny et al, 2012). Other traits not directly related to resource use, such as rRNA operon copy number (Rastogi et al, 2009) and host adaptation (Ettema and Andersson, 2009), may also be conserved at deeper taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…3). With the assumption that soil bacteria possess on average 5 rrn rDNA operons (Rastogi et al, 2009), we found that bacteria abundance estimated by 16S rRNA gene abundance (1.17 Â 10 9 AE 1.38 Â 10 8 genome-equivalent g À1 dry soil for grasslands and 6.7 Â 10 8 AE 1.24 Â 10 8 genomeequivalent g À1 dry soil for crop fields) was approximately as much as double that estimation by FCM counts (6.69 Â 10 8 AE 2.52 Â 10 8 cells g À1 dry soil for grasslands and 4.73 Â 10 8 AE 9.38 Â 10 7 cells g À1 dry soil for crop fields) (Table 3).…”
Section: Other Bacterial Descriptorsmentioning
confidence: 99%